Smart Campus Mobile Application Toward the Development of Smart Cities - Tanweer Alam; Yazeed Mohammed Alharbi; Firas Adel Abusallama; Ahmad Osama Hakeem (Universitas Sanata Dharma, 2020)
Smart Campus is an android mobile application that has strong features to facilitates students, faculties, admins, parents, and managers. It provides a comprehensive integrated solution to improve the overall performance of the college. The use of mobile applications is increasing day by day. We all use mobile application in a lot of things in our daily life. We came up with an idea of building an application that will help the students and faculty member to accesses the system as fast as possible. In this study, we will discuss the problem and propose a solution to it, as we will talk about the planning phase and its component, requirements the functional and non-functional with its Data Flow Diagram, etc. We also design the interfaces. This mobile application will help the students and faculty members to do the tasks in the minimum time.